Comparison of Tunnel Construction Cycle with NTNU Model for the Headrace Tunnel of Seti Khola Hydropower Project - Shrestha, Rukshana; Panthi, Krishna Kanta; Shrestha, Ghan Bahadur (Journal of Engineering and Sciences, 2023)
Achieving smooth and efficient blasting of tunnel walls is a challenging task. Tunneling performance and advancement can best be performed with proper and effective blasting techniques in drill and blast techniques. In this manuscript, the Seti Khola hydropower project’s headrace tunnel’s real-time statistics are used to compare the overall performance of tunnel excavation for the widely used blasting approach. The headrace tunnel’s 663 meters of observed and recorded length comprises rocks with weak to medium blastibility. According to the Q-system, this tunnel section’s rock mass quality class ranges from good to bad. The rock type found has a monotonous sequence of metasandstone and phyllite with quartz partings and discontinuities filled with clay to silt. A variation in the excavation cycle is observed in relation to the presence of different rock mass classes. Ultimately, the NTNU model is compared and analysis is done on the drilling patterns and cycles of tunnel building. It was discovered that using the NTNU model for tunnel excavation presents a significant opportunity to enhance performance.